2021
DOI: 10.3390/ijms22031109
|View full text |Cite
|
Sign up to set email alerts
|

The Chitosan/Agarose/NanoHA Bone Scaffold-Induced M2 Macrophage Polarization and Its Effect on Osteogenic Differentiation In Vitro

Abstract: Chronic immune response to bone implant may lead to delayed healing and its failure. Thus, newly developed biomaterials should be characterized by high biocompatibility. Moreover, it is well known that macrophages play a crucial role in the controlling of biomaterial-induced inflammatory response. Immune cells synthesize also a great amount of signaling molecules that regulate cell differentiation and tissue remodeling. Non-activated macrophages (M0) may be activated (polarized) into two main types of macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
(76 reference statements)
2
23
0
Order By: Relevance
“…In our study, we found that the macrophages in the high Sr groups (especially Sr100%) exhibited larger cell surface area and more pseudopodia ( Fig. 4 A), which was similar to the cell morphology of M2 macrophage described by Kazimierczak et al [ 62 ]. This further confirms that the high Sr specimens significantly increase the polarization of macrophages from M0 to M2 as well as the expression of the various anti-inflammatory genes/factors (IL10 & IL1ra; Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that the macrophages in the high Sr groups (especially Sr100%) exhibited larger cell surface area and more pseudopodia ( Fig. 4 A), which was similar to the cell morphology of M2 macrophage described by Kazimierczak et al [ 62 ]. This further confirms that the high Sr specimens significantly increase the polarization of macrophages from M0 to M2 as well as the expression of the various anti-inflammatory genes/factors (IL10 & IL1ra; Fig.…”
Section: Discussionsupporting
confidence: 89%
“…After biomaterial implantation, several factors have a significant impact on bone tissue repair, inter alia macrophage–osteoblast cross-talk, soluble environmental factors, and surface properties of the implant [ 37 ]. The success of biomaterial implantation depends highly on the implant’s macrophage polarization [ 38 ]. Macrophages are known to be involved in the in vivo biodegradation of resorbable polymers through the release of reactive oxygen intermediates, enzymes, and acids [ 39 ].…”
Section: Post-implantation Complications and The Safety Of Chitosanmentioning
confidence: 99%
“…They can proliferate and differentiate into osteoblasts upon appropriate stimuli. MSCs isolated from bone marrow are regarded as the gold standard [ 14 , 53 , 55 , 57 , 67 , 68 , 73 , 76 , 77 , 79 , 83 , 91 , 94 , 98 , 107 , 108 , 109 ]. MSC-like cells isolated from the stromal vascular fraction of the adipose tissue, namely, adipose-derived stem cells, ASC, are seldom used in selected applications [ 2 , 65 , 72 , 82 , 89 , 104 , 109 , 110 , 111 , 112 ].…”
Section: Biomaterials Osteoinductivity and Osteoconductivitymentioning
confidence: 99%
“…In the vast majority of papers in the literature, the expression levels of one or more genes associated with osteoblast differentiation are usually evaluated by quantitative real-time PCR (qRT-PCR) and/or Western blot and/or immunofluorescence analysis and/or ELISA assay [ 14 , 55 , 57 , 58 , 60 , 62 , 64 , 65 , 68 , 69 , 70 , 72 , 73 , 76 , 77 , 79 , 80 , 82 , 83 , 84 , 86 , 87 , 89 , 90 , 91 , 94 , 96 , 98 , 100 , 108 , 109 , 113 ]. Table 3 reports the most representative osteogenic genes usually analyzed.…”
Section: Biomaterials Osteoinductivity and Osteoconductivitymentioning
confidence: 99%